Assessment of the prevalence and spatial distribution of the posterior superior alveolar artery within the maxillary sinus wall utilizing CBCT imaging - Maha Maqbool; Ahmad Danyal; Zubair Ahmad Khan; Muhammad Haseeb; Usman Manzoor; Nuvaira Ijaz (Journal of University Medical & Dental College)
BACKGROUND & OBJECTIVE: The posterior superior alveolar (PSAA) artery plays a crucial role in supplying blood to the lateral wall of the maxillary sinus. This artery is of particular significance while performing procedures that involve the maxillary sinus. Our current study aimed to localize this artery and record its distance from a particular landmark: the maxillary sinus floor in patients reporting to a dental teaching hospital.